CONTENT OF THE AUDITING COURSE. - Bacas, Paul E. (The Accounting Review, 1939)
Abstract This article focuses on the basic content and needs of the auditing course. It describes that auditing is considered as the application of accounting principles to the various transactions which come before the public accountant in his daily work. It is advised that instruction in auditing should essentially include not only the application of the principles to a certain transaction but the application of the principles to the same type of transaction under varying conditions and circumstances. As an advanced subject auditing is restricted to those students who have satisfactorily completed courses in other accounting subjects such as bookkeeping, theory of accounting and accounting problems. It should not include detailed discussions of principles of accounting, or give any basic instruction in such principles. The course in auditing as distinguished from other courses in accounting and many other subjects should emphasize continually the habit of clear thinking.